Heart rate variability activity in soccer athletes after a musculoskeletal injury - Flores, Gonçalo (2024)
Objectives: The aim of this study is to analyse the adaptations of the autonomic nervous system after a musculoskeletal injury, obtained by measuring heart rate variability in athletes. It was hypothesized that there is an alteration in heart rate variability after a musculoskeletal injury. Study design: Cohort study. Subjects: 15 semi-professional soccer players from three football teams, aged between 21 and 33 (mean age: 29.4 ± 3.31 years), with a recent musculoskeletal injury. Methods: Heart rate variability was collected using the Polar m200 and the chest strap H10 in two moments: within 72 h after the injury and between 5 and 7 days after full return-to-play. Results: Results show differences between T1 and T2 (p ≤ 0.05) in low-frequency power (n.u.) (p = 0.001) and high-frequency power (n.u.) (p = 0.001), in low-frequency/high-frequency ratio (p = 0.001) and in high-frequency power (ms2) (p = 0.017) measures. No statistical differences were found in low-frequency power (ms2) (p = 0.233). The low frequency power (n.u.) was significantly lower after injury compared with LF power (n.u.) values after full return-to-play. In high-frequency power there was a significant difference between both moments with high values after injury. Conclusions: The use of heart rate variability therefore seems to be promising to detect an imbalance in the autonomic nervous system and help clinical departments to identify a possible non-traumatic musculoskeletal injury. Further research should be performed considering a wide range of musculoskeletal injuries and to establish baseline values of the athletes.